Optimization of zirconia surface textured designs using Nd:Yag laser for biomedical applications - Marques, Ana Cristina Ribeiro (2021)
The development of surface textured designs has influence in primary stability of surgically placed implants since a textured surface allows to firmer mechanical link to the surrounding tissue. Laser technology has been investigated to develop new surface designs on green zirconia compacts by cold pressing. Nd:Yag laser were used to produce several strategies and different laser parameters (laser power, speed and laser passages) were tested to evaluate their impact on cavities geometry and depth. The surface texture designs were analysed by Scanning Electron Microscopy (SEM) and regular geometries such as cavities or pillars were observed. The distance between lines have a strong impact on texturing quality and should be combined with optimum power and speed conditions. Regarding the optimized conditions, several surface textured patterns were created in both green and sintered zirconia compacts. This study allowed to conclude that only some texturing strategies are suitable to obtain high quality surface textured patterns. Otherwise, the remaining strategies are potential solutions for obtaining high quality machined structures (laser does not machine cavities but crosses the entire bulk). High strength zirconia scaffolds were machined by laser and CNC machining technologies and the two promising technologies were compared.